"Conceal my Body so that I can Protect the State": The Making of the Mysterious Woman in Daoism and Water Margin. (2nd July 2016) - Liu, Peng
Abstract : Protecting fictional heroes against misfortune and helping them defeat demonic enemies, the Mysterious Woman of the Nine Heavens proves to be a crucial figure in the Ming novel Water Margin . Her divine power and military wisdom pique our interest, inviting us to discover her true identity and investigate the process of her creation. This article shows how a set of related Daoist texts strengthens her role as a warrior protectress by giving prominence to her magic of concealing the body 隱身 ( yinshen ) and to magic concerning the worship of the Northern Dipper. The association of these two types of magic with the Mysterious Woman indicates the nature of this deity as a mixture of Daoist ideas that are in turn assimilated into the novel to serve narrative functions. In this process, the novel codes religious ideas into its own language and portrays the Mysterious Woman as an internal author who controls the knowledge of the characters' destinies. Her intervention in human affairs is restaged in a novel setting. The novel functions as part of a cultural mechanism that creates new stories about this ancient goddess.